1974
DOI: 10.1111/j.1467-1770.1974.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There a “Natural Sequence” in Adult Second Language Learning?

Abstract: The Bilingual Syntax Measure (Burt, Dulay, and Hernandez 1973) was administered to 73 adult learners of English as a second language in order to investigate accuracy of usage for eight English functors. It was found that there is a highly consistent order of relative difficulty in the use of the functors across different language backgrounds, indicating that learners are experiencing intra‐language difficulties. Also, the adult results agreed with those obtained by Dulay and Burt (1973) for 5 to 8 year old chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
214
1
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(248 citation statements)
references
References 8 publications
21
214
1
12
Order By: Relevance
“…"For instance,the morpheme studies showed that the order of acquisition of a group of English morphemes was the same for children and adults" (Bailey, Madden, & Krashen, 1974). Adult L2 acquisition is very similar to child L1 acquisition as some researchers such as Dulay, Burt and Krashen (1982) argued, and in this process L1 background of learners does not have any effect on L2.…”
Section: Theory and Practice In Language Studies 2113mentioning
confidence: 97%
“…"For instance,the morpheme studies showed that the order of acquisition of a group of English morphemes was the same for children and adults" (Bailey, Madden, & Krashen, 1974). Adult L2 acquisition is very similar to child L1 acquisition as some researchers such as Dulay, Burt and Krashen (1982) argued, and in this process L1 background of learners does not have any effect on L2.…”
Section: Theory and Practice In Language Studies 2113mentioning
confidence: 97%
“…Bailey, Madden and Krashen (1974) found a common acquisition order for both Spanish and non-Spanish adults which differed from the L1 order. The acquisition order Hakuta (1974) obtained for a Japanese girl, however, did not match the orders obtained by Dulay andBurt (1973, 1974).…”
Section: Morpheme Order Studiesmentioning
confidence: 97%
“…Morpheme studies have shown a natural sequence of acquisition of grammatical morphemes for L2 very similar to that for L1 (Dulay and Burt, 1978;Bailey, Madden, and Krashen, 1978). There is a question as to whether the natural order is disrupted by learning because most of the L2 studies in the United States look at a mixed type of learner, who is receiving formal instruction while living in a naturalistic English-speaking environment.…”
Section: Evidence For the Monitor Modelmentioning
confidence: 99%